Optimized design of the 4TSQ-2 sugar beet top cutting machine - Wang, Fangyan; Zhang, Zhenyu; Pan, Yongfei; Yun, Yuliang; Wang, Dongwei (International Journal of Agricultural and Biological Engineering, 2022)
To solve the problems faced by 4TSQ-2 sugar beet top cutting machine, i.e. large structure, high power consumption and high manufacturing cost, the multi-roller mechanism for leaves removal and fixed-thickness cutting method was studied. Using five-factor and two-level tests, the structure configuration of the leaf removal device was optimized, and the scheme of two roller shafts defoliation, the roller shaft rotation speed of 800 r/min and the forward speed of 0.8 m/s were determined. Through the working process and mechanical analysis of the top cutting device, the cutting device with the slant profiling plate structure characterized by a profiling angle of 25°-45° for the profiling plate and a cutting angle of 20°-40° was studied. With the two-factor and three-level experiments, the profiling angle of profiling plate of the top cutting device was 35°, and the cutting angle was 30°. Compared with the 4TSQ-2 sugar beet top cutting machine before optimization, the structure size of the machine was reduced by 30%, the weight was reduced by 15%, the cost was reduced by 25%, the qualified rate of top cutting wad was increased by 2.6%, and the push over rate of sugar beet was reduced by 0.5%. Besides, each index met the index requirements of beet top cutting harvest.Keywords: beet harvest, leaves cleaning, top cutting, structure, optimizationDOI: 10.25165/j.ijabe.20221502.6981Citation: Wang F Y, Zhang Z Y, Pan Y F, Yun Y L, Wang D W. Optimized design of the 4TSQ-2 sugar beet top cutting machine. Int J Agric & Biol Eng, 2022; 15(2): 111–116.